2022
DOI: 10.3389/fnbeh.2022.775796
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives Modulate the Relationship Between Resting Brain Activity, Amygdala Connectivity and Emotion Recognition – A Resting State fMRI Study

Abstract: Recent research into the effects of hormonal contraceptives on emotion processing and brain function suggests that hormonal contraceptive users show (a) reduced accuracy in recognizing emotions compared to naturally cycling women, and (b) alterations in amygdala volume and connectivity at rest. To date, these observations have not been linked, although the amygdala has certainly been identified as core region activated during emotion recognition. To assess, whether volume, oscillatory activity and connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary findings suggest that androgenicity of progestins affects brain structure [72], likelihood of mood-related side effects [73] and emotion recognition performance [74]. Furthermore, the relation between RSFC and emotion recognition seems to be differently modulated by OC androgenicity [36]. Therefore, controlling for progestin types, larger sample sizes for stratification or coding of the estrogenic, progestogenic and androgenic properties to reflect biological potencies using information from in vivo bioassays and/or receptor studies [75] is recommendable to account more systematically for OC-related side-effects on the brain as well as socio-affective functions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, altered hormone-related RSFC may indeed be part of the neural mechanisms underlying hormone-related mood changes. Similarly, OC intake appears to modulate the relationship between amygdala RSFC and emotion recognition performance differently than the menstrual cycle[36]. Therefore, hormonal influences on brain regions involved in emotion recognition may lead to hormone-related differences in emotion recognition performance.…”
mentioning
confidence: 99%